ETHANOL CONTENT OF FERMENTED JACKFRUIT SKIN (Artocarpus haterophyllus Lmk) ON DIFFERENT SALT LEVELS - Almira Ulimaz (Nusantara Hasana Berdikari, 2021)
Jackfruit skin often considered as by product immediately after the fruit being used or consumed. However, if processed further this jackfruit skin can actually be fermented and has the potential to be a biofuel. Traditionally wastewater from fermented jackfruit skin can produce bioethanol. Bioethanol is ethanol (ethyl alcohol) whose production process uses natural raw materials and biological processes. Considering the current condition, namely fossil fuels in Indonesia are getting scarce, especially motor vehicle fuel, so naturally this bioethanol from fermented jackfruit skin has the opportunity to become a substitute energy. This study aimed to determine the ethanol content of jackfruit skin fermentation. Anaerobic fermentation was done with the addition of 600 ofater and one month incubation. The resulting bioethanol levels were measured with an alcohol meter. The results showed that different levels of salt produced an amount of ethanol which was also different from the fermentation of jackfruit skin. The difference in the amount of ethanol produced is thought to be due to the influence of the growth of lactic acid bacteria.